P-i-n type perovskite solar cell based on light-dark reversible isomeric molecule stress release light cycle stability and preparation method of p-i-n type perovskite solar cell based on light-dark reversible isomeric molecule stress release light cycle stability

By introducing light-dark reversible isomeric molecules as additives into perovskite solar cells, the perovskite lattice stress is dynamically adjusted, which solves the stability problem of perovskite solar cells under light cycle conditions and achieves high performance and long-term performance. life of photovoltaic devices.

CN119343022AActive Publication Date: 2025-01-21HENAN UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411508807.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-21
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

Perovskite solar cells are insufficient in outdoor environments, especially under light cycle conditions, resulting in rapid degradation and shortened lifetime.

Method used

Introducing light-dark reversible isomeric molecules as additives to the perovskite precursor solution regulates the perovskite lattice stress through a dynamic stress release mechanism, and coordinates molecular π-π interactions and Lewis acid-base reactions to repair damage.

Benefits of technology

It significantly improves the energy conversion efficiency of perovskite solar cells, improves light cycle stability, and extends the life of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343022A_ABST
    Figure CN119343022A_ABST
Patent Text Reader

Abstract

The invention discloses a p-i-n type perovskite solar cell based on light-dark reversible isomeric molecule stress release light cycle stability and a preparation method thereof, and belongs to the field of solar cells. According to the preparation method, a series of light-dark reversible isomeric molecules are used as the grain boundary buffer layer of the perovskite solar cell, the anti-expansion characteristic of the molecules can effectively buffer expansion and shrinkage of the perovskite thin film in a light-dark circulation state, and thin film degradation caused by expansion and shrinkage of the perovskite thin film is inhibited. The passivation group at one end can form coordination with Pb < 2 + >, so that ordered growth of the thin film is ensured, the defect density is reduced, the charge transfer rate is improved, and the efficient and stable preparation of the p-i-n type perovskite solar cell is further realized. According to the method, the preparation method for improving the p-i-n type perovskite solar cell in the actual light and dark cycle operation environment is provided, and the method plays a great role in promoting the commercialization progress of the p-i-n type perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solar cells, and in particular relates to a PIN-type perovskite solar cell based on light-dark reversible isomerized molecular stress release and light cycle stability and a preparation method thereof. Background Art

[0002] Perovskite solar cells have become a breakthrough technology in the field of photovoltaics, with high efficiency and low production cost. However, their stability is a major challenge to commercialization, especially under actual operating conditions. Although recent advances have improved the resistance of perovskite solar cells to light, heat, bias and humidity, their stability in outdoor environments is still not well improved due to the large variation in daily and seasonal weather conditions.

[0003] When simulating outdoor conditions, high-energy UV rays can cause irreversible damage and significantly degrade device performance. In addition, cyclic lighting produces more adverse effects and accumulates harmful effects, ultimately shortening the lifetime and reliability of perovskite solar cells. Here, standard accelerated aging tests, such as continuous light soaking, are inadequate to simulate outdoor cycling processes. Therefore, we employ light-dark cycling tests to simulate real-world day-night alternation conditions to reveal how rapid indoor light cycling accelerates device aging and better estimate the long-term stability of perovskite solar cells in the real world. Light cycling induces the accumulation of internal stress in the absorber, leading to crystal fragmentation at grain boundaries, which in turn causes lattice strain in perovskite films and leads to rapid degradation of perovskite solar cells. To address these issues, we develop a grain boundary elastic strategy using photoswitchable isomers triggered by UV light for dynamic stress release to improve device durability during light cycling. Summary of the invention

[0004] The purpose of the present invention is to provide a PIN-type perovskite solar cell based on light-dark reversible heterogeneous molecular stress release and photocycle stability and a preparation method thereof, which introduces a series of materials with dynamic stress release characteristics as perovskite precursor solution additives to adjust the perovskite lattice stress during the photocycle process, and coordinate molecular π-π interactions, Lewis acid-base reactions, etc. to repair the perovskite damage caused by the photocycle. The energy conversion efficiency of the photovoltaic device prepared by this strategy is significantly improved, and it also has excellent photocycle stability.

[0005] In order to achieve the above object, the present invention provides the following technical solutions: A method for preparing a PIN-type perovskite solar cell based on light-dark reversible isomerized molecular stress release and light cycle stability, the preparation method comprising the following steps: (1) spin coating a mixed ethanol solution of [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz) and [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz) on a washed, dried and ozone-treated substrate to obtain a hole selective layer; (2) doping the light-dark reversible isomerization molecules into the original perovskite precursor solution to obtain an optimized perovskite precursor solution; (3) depositing the optimized perovskite precursor solution and annealing to obtain a perovskite layer; (4) [6,6]-phenyl-C61-butyric acid methyl ester (PC) was prepared on the perovskite layer by spin coating, scraping, screen printing, etc. 61 BM) or by evaporation or inkjet printing to prepare fullerene (C 60 ), a uniform electron transport layer is obtained; (5) Prepare a 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) modification layer on the electron transport layer by evaporation or inkjet printing or obtain tin oxide (SnO 2 ) Modification layer; (6) In BCP or SnO 2 The cathode metal electrode is prepared on the modified layer by evaporation or inkjet printing.

[0006] Furthermore, the substrate in step (1) is an ITO or FTO conductive substrate, the total concentration of 2PACz and Me-4PACz in the ethanol solution is 0.1-0.5 mg / mL (the mass ratio of 2PACz to Me-4PACz is 1:1-3), and the spin coating amount is 10-20 μL / cm 2 The spin coating speed is 3000~5000 r / min, the annealing temperature is 100~120 ℃, and the annealing time is 5~10min. The thickness of the hole selection layer is 2~10 nm.

[0007] Furthermore, the light-dark reversible isomerized molecular material in step (2) is at least one of azobenzene (Abz), azobenzene-4-benzoic acid (Ca-Abz), azobenzene-4,4-dicarboxylic acid (Dca-Abz) and 4-(phenylazo)benzenesulfonic acid (SA-Abz) that are triggered by ultraviolet light to release dynamic stress. The molecular formulas of azobenzene (Abz), azobenzene-4-benzoic acid (Ca-Abz), azobenzene-4,4-dicarboxylic acid (Dca-Abz) and 4-(phenylazo)benzenesulfonic acid (SA-Abz) are shown in Figure 1 .

[0008] Preferably, the concentration of the light-dark reversible isomerization molecule doped in the perovskite precursor is 1-2 mg / mL.

[0009] Furthermore, the original perovskite precursor solution in step (2) is specifically Cs 0.05 MA 0.1 FA 0.85 PbI 3 , the perovskite concentration is 1.5~2 mol / L. Cs 0.05 MA 0.1 FA 0.85 PbI 3 The preparation process of the perovskite precursor solution is as follows: lead iodide (PbI 2 ), formamidine iodide (FAI), methylamine iodide (MAI), methylamine chloride (MACl) and cesium iodide (CsI) are dissolved in 1 mL of a mixed solvent consisting of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF) in proportion and stirred evenly to obtain a perovskite precursor solution. The volume ratio of DMSO to DMF in the mixed solvent is 1:4.

[0010] Furthermore, in the step (3), the perovskite annealing temperature is 100-120° C., and the annealing time is 20-45 min.

[0011] Preferably, the spin coating amount of the perovskite precursor solution is 10-20 μL / cm 2 , the spin coating speed is 3000~5000 r / min. Spin the anti-solvent 15~25s before the end of spin coating, the anti-solvent is chlorobenzene. The spin coating amount of the anti-solvent is 15~35μL / cm 2 .

[0012] Preferably, in step (3), the thickness of the perovskite layer is 500-700 nm.

[0013] Furthermore, in the step (4), C 60 or PC 61 The thickness of the BM electron transport layer is 30~40 nm.

[0014] Furthermore, in step (5), BCP or SnO 2 The thickness of the modified layer is 10~25 nm.

[0015] Furthermore, in the step (6), the cathode electrode is Au, Ag or Cu, and the electrode thickness is 70-110 nm.

[0016] The preparation method of the present invention is based on light-dark reversible heterogeneous molecular stress release and photocyclic stability of PIN-type perovskite solar cell.

[0017] Beneficial effects of the present invention: The present invention proposes a light-dark reversible heterogeneous molecular stress-releasing photocycle-stable perovskite solar cell, which introduces a series of materials with light-dark reversible heterogeneous properties as additives into the perovskite precursor solution. These materials regulate the perovskite stress in the photocycle through reversible heterogeneous properties, thereby repairing the defect-dominated perovskite grain boundary damage caused by thermal expansion and contraction under the photocycle. The finally prepared perovskite photovoltaic device has excellent photocycle stability while achieving high energy conversion efficiency. The present invention is conducive to an in-depth understanding of the correlation mechanism between perovskite lattice strain and defects and perovskite operating stability under outdoor conditions, and provides a new idea for the preparation of efficient and photocycle-stable perovskite photovoltaic devices. This strategy is of great significance for promoting the commercial development of perovskite solar cells and comprehensively improving the performance of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is the molecular formula of azobenzene (Abz), azobenzene-4-benzoic acid (Ca-Abz), azobenzene-4,4-dicarboxylic acid (Dca-Abz) and 4-(phenylazo)benzenesulfonic acid (SA-Abz); Figure 2 A schematic diagram of the structure of a pin-type perovskite solar cell prepared by the preparation method of the present invention; Figure 3 Example 1 Perovskite solar cell device using azobenzene (Abz) as an additive JV curve; Figure 4 Example 2: Perovskite solar cell device using azobenzene-4-benzoic acid (Ca-Abz) as an additive JV curve; Figure 5 Example 3: Perovskite solar cell device with azobenzene-4,4-dicarboxylic acid (Dca-Abz) as an additive JV curve; Figure 6 Example 4: Perovskite solar cell device with 4-(phenylazo)benzenesulfonic acid (SA-Abz) as an additive JV curve; Figure 7 Perovskite solar cell device for comparative example 1 JV curve; Figure 8 The light cycle stability curves of the perovskite solar cell devices of Examples 1-4 and Comparative Example 1. DETAILED DESCRIPTION

[0019] The present invention is further described below in conjunction with specific embodiments, but the embodiments are only exemplary and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention can be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the protection scope of the present invention.

[0020] Example 1 A method for preparing a PIN-type perovskite solar cell based on light-dark reversible heterogeneous molecular stress release and photocyclic stability comprises the following steps: (1) A 2.5 cm*2.5 cm FTO transparent conductive substrate was first scrubbed on both sides with glass detergent, then ultrasonically cleaned with ultrapure water, acetone and anhydrous ethanol for 15 min each, and then dried in an oven at 60 °C; (2) Lead iodide (PbI 2 ), formamidine iodide (FAI), methylamine iodide (MAI), methylamine chloride (MACl) and cesium iodide (CsI) were dissolved in 1 mL of a mixed solvent consisting of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF) (volume ratio of 1:4), and 1 mg of Abz molecular material was added at the same time. The mixture was stirred for 8 hours until uniform, and a Cs with a concentration of 1.5 mmol / mL was obtained. 0.05 MA 0.1 FA 0.85 PbI 3 And the perovskite precursor solution with Abz as an additive; (3) Dissolve 0.17 mg 2PACz and 0.33 mg Me-4PACz in 3 mL ethanol and stir evenly to obtain a hole selective layer solution; (4) The FTO that had been cleaned in step (1) was treated with ozone for 30 min, 100 μL of the hole selection layer solution was added dropwise, and the mixture was rotated at 3000 r / min for 30 s, followed by annealing at 100°C for 10 min to obtain a solidified hole selection layer with a thickness of 3 to 5 nm; (5) 100 μL of the perovskite precursor solution was dripped onto the substrate obtained in step (4), and the substrate was rotated at 4000 r / min for 40 s. After 20 s, 200 μL of anti-solvent (chlorobenzene) was dripped, and then annealed at 100 °C for 45 min to obtain a perovskite layer with a thickness of about 600 nm. (6) Preparation of fullerene C by evaporation method 60 Electron transport layer, with a thickness of 40 nm; (7) A modified layer of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) was prepared by evaporation method with a thickness of 15 nm; (8) The cathode electrode Ag is prepared by evaporation method with a thickness of 100 nm and a structure as shown below: Figure 2 As shown, from bottom to top, they are FTO substrate, hole selection layer, perovskite layer, C 60 Layer, BCP layer and Ag electrode layer, perovskite solar cell device under AM1.5G simulated sunlight JV Curve like Figure 3 As shown, its PCE is 26.38%, V OC is 1.19 V, J SC 26.3mA / cm 2 , FF is 84.3%.

[0021] Example 2 A method for preparing a PIN-type perovskite solar cell based on light-dark reversible heterogeneous molecular stress release and photocyclic stability comprises the following steps: (1) A 2.5 cm*2.5 cm FTO transparent conductive substrate was first scrubbed on both sides with glass detergent, then ultrasonically cleaned with ultrapure water, acetone and anhydrous ethanol for 15 min each, and then dried in an oven at 60°C; (2) Lead iodide (PbI 2 ), formamidine iodide (FAI), methylamine iodide (MAI), methylamine chloride (MACl) and cesium iodide (CsI) were dissolved in 1 mL of a mixed solvent consisting of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF) (volume ratio of 1:4), and 1 mg of Ca-Abz molecular material was added at the same time. The mixture was stirred for 8 hours until uniform, and a CsI with a concentration of 1.5 mmol / mL was obtained. 0.05 MA 0.1 FA 0.85 PbI 3 And a perovskite precursor solution with Ca-Abz as an additive; (3) Dissolve 0.17 mg 2PACz and 0.33 mg Me-4PACz in 3 mL ethanol and stir evenly to obtain a hole selective layer solution; (4) The FTO that had been cleaned in step (1) was treated with ozone for 30 min, 100 μL of the hole selection layer solution was added dropwise, and the mixture was rotated at 3000 r / min for 30 s, followed by annealing at 100°C for 10 min to obtain a solidified hole selection layer with a thickness of 3 to 5 nm; (5) 100 μL of the perovskite precursor solution was dripped onto the substrate obtained in step (4), and the substrate was rotated at 4000 r / min for 40 s. After 20 s, 200 μL of anti-solvent (chlorobenzene) was dripped, and then annealed at 100 °C for 45 min to obtain a perovskite layer with a thickness of about 600 nm. (6) Preparation of fullerene C by evaporation method 60 Electron transport layer, with a thickness of 40 nm; (7) A modified layer of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) was prepared by evaporation method with a thickness of 15 nm; (8) The cathode electrode Ag was prepared by evaporation method with a thickness of 100 nm. Under AM1.5G simulated sunlight, the perovskite solar cell device JV Curve like Figure 4 As shown, its PCE is 27.10%, V OC is 1.20 V, J SC 26.5 mA / cm 2 , FF is 85.2%.

[0022] Example 3 A method for preparing a PIN-type perovskite solar cell based on light-dark reversible heterogeneous molecular stress release and photocyclic stability comprises the following steps: (1) A 2.5 cm*2.5 cm FTO transparent conductive substrate was first scrubbed on both sides with glass detergent, then ultrasonically cleaned with ultrapure water, acetone and anhydrous ethanol for 15 min each, and then dried in an oven at 60°C; (2) Lead iodide (PbI 2 ), formamidine iodide (FAI), methylamine iodide (MAI), methylamine chloride (MACl) and cesium iodide (CsI) were dissolved in 1 mL of a mixed solvent consisting of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF) (volume ratio of 1:4), and 1 mg of Dca-Abz molecular material was added at the same time. The mixture was stirred for 8 hours until uniform, and a CsI with a concentration of 1.5 mmol / mL was obtained. 0.05 MA 0.1 FA 0.85 PbI 3 And a perovskite precursor solution with Dca-Abz as an additive; (3) Dissolve 0.17 mg 2PACz and 0.33 mg Me-4PACz in 3 mL ethanol and stir evenly to obtain a hole selective layer solution; (4) The FTO that had been cleaned in step (1) was treated with ozone for 30 min, 100 μL of the hole selection layer solution was added dropwise, and the mixture was rotated at 3000 r / min for 30 s, followed by annealing at 100°C for 10 min to obtain a solidified hole selection layer with a thickness of 3 to 5 nm; (5) 100 μL of the perovskite precursor solution was dripped onto the substrate obtained in step (4), and the substrate was rotated at 4000 r / min for 40 s. After 20 s, 200 μL of anti-solvent (chlorobenzene) was dripped, and then annealed at 100 °C for 45 min to obtain a perovskite layer with a thickness of about 600 nm. (6) Preparation of fullerene C by evaporation method 60 Electron transport layer, with a thickness of 40 nm; (7) A modified layer of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) was prepared by evaporation method with a thickness of 15 nm; (8) The cathode electrode Ag was prepared by evaporation method with a thickness of 100 nm. Under AM1.5G simulated sunlight, the perovskite solar cell device JV Curve like Figure 5 As shown, its PCE is 26.80%, V OC is 1.20 V, J SC 26.4 mA / cm 2 , FF is 84.6%.

[0023] Example 4 A method for preparing a PIN-type perovskite solar cell based on light-dark reversible heterogeneous molecular stress release and photocyclic stability comprises the following steps: (1) A 2.5 cm*2.5 cm FTO transparent conductive substrate was first scrubbed on both sides with glass detergent, then ultrasonically cleaned with ultrapure water, acetone and anhydrous ethanol for 15 min each, and then dried in an oven at 60°C; (2) Lead iodide (PbI 2 ), formamidine iodide (FAI), methylamine iodide (MAI), methylamine chloride (MACl) and cesium iodide (CsI) were dissolved in 1 mL of a mixed solvent consisting of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF) (volume ratio of 1:4), and 1 mg of SA-Abz molecular material was added at the same time. The mixture was stirred for 8 hours until uniform, and a CsI with a concentration of 1.5 mmol / mL was obtained. 0.05 MA 0.1 FA 0.85 PbI 3And the perovskite precursor solution with SA-Abz as an additive; (3) Dissolve 0.17 mg 2PACz and 0.33 mg Me-4PACz in 3 mL ethanol and stir evenly to obtain a hole selective layer solution; (4) The FTO that had been cleaned in step (1) was treated with ozone for 30 min, 100 μL of the hole selection layer solution was added dropwise, and the mixture was rotated at 3000 r / min for 30 s, followed by annealing at 100°C for 10 min to obtain a solidified hole selection layer with a thickness of 3 to 5 nm; (5) 100 μL of the perovskite precursor solution was dripped onto the substrate obtained in step (4), and the substrate was rotated at 4000 r / min for 40 s. After 20 s, 200 μL of anti-solvent (chlorobenzene) was dripped, and then annealed at 100 °C for 45 min to obtain a perovskite layer with a thickness of about 600 nm. (6) Preparation of fullerene C by evaporation method 60 Electron transport layer, with a thickness of 40 nm; (7) A modified layer of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) was prepared by evaporation method with a thickness of 15 nm; (8) The cathode electrode Ag was prepared by evaporation method with a thickness of 100 nm. Under AM1.5G simulated sunlight, the perovskite solar cell device JV Curve like Figure 6 As shown, its PCE is 27.13%. V OC is 1.20 V, J SC 26.50 mA / cm 2 , FF is 85.3%.

[0024] Comparative Example 1 The preparation method of a conventional inverse perovskite solar cell comprises the following steps: (1) A 2.5 cm*2.5 cm FTO transparent conductive substrate was first scrubbed on both sides with glass detergent, then ultrasonically cleaned with ultrapure water, acetone and anhydrous ethanol for 15 min each, and then dried in an oven at 60 °C; (2) Lead iodide (PbI 2), formamidine iodide (FAI), methylamine iodide (MAI), methylamine chloride (MACl), and cesium iodide (CsI) were dissolved in 1 mL of a mixed solvent consisting of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF) (volume ratio of 1:4) and stirred for 8 hours until uniform to obtain a CsI solution with a concentration of 1.5 mmol / mL. 0.05 MA 0.1 FA 0.85 PbI 3 And the perovskite precursor solution with Abz as an additive; (3) Dissolve 0.17 mg 2PACz and 0.33 mg Me-4PACz in 3 mL ethanol and stir evenly to obtain a hole selective layer solution; (4) The FTO that had been cleaned in step (1) was treated with ozone for 30 min, 100 μL of the hole selection layer solution was added dropwise, and the mixture was rotated at 3000 r / min for 30 s, followed by annealing at 100°C for 10 min to obtain a solidified hole selection layer with a thickness of 3 to 5 nm; (5) 100 μL of the perovskite precursor solution was dripped onto the substrate obtained in step (4), and the substrate was rotated at 4000 r / min for 40 s. After 20 s, 200 μL of anti-solvent (chlorobenzene) was dripped, and then annealed at 100 °C for 45 min to obtain a perovskite layer with a thickness of about 600 nm. (6) Preparation of fullerene C by evaporation method 60 Electron transport layer, with a thickness of 40 nm; (7) A modified layer of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) was prepared by evaporation method with a thickness of 15 nm; (8) The cathode electrode Ag was prepared by evaporation method with a thickness of 100 nm. Under AM1.5G simulated sunlight, the perovskite solar cell device JV Curve like Figure 7 As shown, its PCE is 24.95%. V OC is 1.16 V, J SC 26.2 mA / cm 2 , FF is 82.1%.

[0025] Table 1 By comparing Examples 1-4 with Comparative Example 1, it can be seen that the energy conversion efficiency of the perovskite solar cell device using the light-dark reversible heterogeneous material as an additive is significantly improved compared with the traditional original device, up to 27.13%. At the same time, the perovskite device improved by the light-dark reversible heterogeneous material also shows excellent light cycle stability, as shown in Table 1, Figures 3 to 8 As shown, the best device based on SA-Cbz exhibited the best device efficiency and photocycle stability (12 h light and 12 h dark), and its stability maintained 98% of the initial value, while Comparative Example 1 (standard) only maintained 56% of the initial value, while Abz, Ca-Abz and Dca-Abz maintained 83%, 92% and 96% of the initial value, respectively.

Claims

1. A method for preparing a PIN-type perovskite solar cell based on light-dark reversible isomerization molecular stress release and light cycle stability, characterized in that: The following steps are involved: (1) Spin coating a mixed ethanol solution of 2PACz and Me-4PACz on a washed, dried and ozone-treated substrate to obtain a hole selective layer; (2) doping the light-dark reversible isomerization molecules into the original perovskite precursor solution to obtain an optimized perovskite precursor solution; (3) depositing the optimized perovskite precursor solution and annealing to obtain a perovskite layer; (4) Preparation of PC on perovskite layer 61 BM or C 60 layer to obtain a uniform electron transport layer; (5) Preparing a BCP or SnO2 modified layer on the electron transport layer; (6) Prepare cathode metal electrode on BCP or SnO2 modified layer.

2. The preparation method according to claim 1, characterized in that: The substrate in step (1) is an ITO or FTO conductive substrate; the total concentration of 2PACz and Me-4PACz in the ethanol solution mixed with 2PACz and Me-2PACz is 0.1-0.5 mg / mL, the mass ratio of 2PACz to Me-4PACz is 1:(1-3), the annealing temperature of the hole selection layer is 100-120°C, and the annealing time is 5-10 min.

3. The preparation method according to claim 1, characterized in that: The light-dark reversible isomer molecule in step (2) is at least one of azobenzene (Abz), azobenzene-4-benzoic acid (Ca-Abz), azobenzene-4,4-dicarboxylic acid (Dca-Abz) and 4-(phenylazo)benzenesulfonic (SA-Abz) acid.

4. The preparation method according to claim 1, characterized in that: In the step (2), the concentration of the light-dark reversible isomerization molecule in the perovskite precursor solution is 1-2 mg / mL; the original perovskite precursor solution is specifically Cs 0.05 MA 0.1 FA 0.85 The concentration of the PbI3 perovskite precursor solution is 1.5~2 mol / L, and the solvent is a mixed solvent of DMSO and DMF with a volume ratio of 1:

4.

5. The preparation method according to claim 1, characterized in that: In step (3), the annealing temperature is 100-120°C, and the annealing time is 20-45 min.

6. The preparation method according to claim 1, characterized in that: The thickness of the perovskite film in step (3) is 500-700 nm.

7. The preparation method according to claim 1, characterized in that: In step (4) described above, PC 61 BM or C 60 The thickness of the electron transport layer is 30~40 nm.

8. The preparation method according to claim 1, characterized in that: In the step (5), the thickness of the BCP or SnO2 modification layer is 10-25 nm.

9. The preparation method according to claim 1, characterized in that: In the step (6), the cathode electrode is Au, Ag or Cu, and the electrode thickness is 70-110 nm.

10. The preparation method according to any one of claims 1 to 9 produces a light-dark reversible heterogeneous molecular stress release photocyclically stable PIN-type perovskite solar cell.

Citation Information

Patent Citations

  • Flexible perovskite solar cell and preparation method thereof

    CN114203910A

  • Method for improving efficiency and stability of perovskite solar cell

    CN114639782A

  • Lead-tin mixed perovskite solar cell based on self-assembled single layer and preparation method thereof

    CN117337115A

  • Perovskite preparation method for accelerating crystallization rate and flexible device thereof

    CN117596996A

  • Trans-perovskite solar cell for repairing thermally induced damage of perovskite based on self-healing characteristic material and preparation method of trans-perovskite solar cell

    CN118591247A